Hurdles on the way to the diagnosis of asthma and successful therapy - Hausen, Thomas (Pneumologie, 2024)
There are many potential hurdles, obviously at the forefront of patient care which may impede the correct and early diagnosis of asthma, as well as successful, appropriate treatment. Although the illness is often accompanied by many typical signs which may enable a rapid diagnosis, these are often overlooked or misinterpreted. Symptoms may not be recognised or confused with others, such as respiratory infections, and inappropriate diagnostic tests used. Inappropriate therapy (absent or insufficient dosage of a topical anti-inflammatory and/or exclusive usage of a short-acting beta-agonist) and failure to adapt therapy may further impede the patient’s chance to live without symptoms.
Keywords: asthma; diagnosis; bronchodilator test; inhalation technique; therapy adaptation